Implementation of the hidden curriculum in the formation of the religious character of students - Ulfa Fitria; Nur Khalimah (Curricula: Journal of Curriculum Development, 2024)
The educational curriculum applied in Islamic boarding schools to educate students' character is limited to using a written curriculum system and a hidden curriculum applied in teaching activities at Islamic boarding schools. This study aims to explain the hidden curriculum policy (hidden curriculum in the Darussalam Blokagung Banyuwangi Islamic boarding school). This study uses a qualitative descriptive method, which emphasizes field observation. This method aims to obtain complete and in-depth information by collecting data through observations, interviews, and documentation. As a result of this study, the researcher found that the hidden curriculum applied at the Darussalam Blokagung Islamic boarding school has been implemented since the founders of the Islamic boarding school, namely KH. Mukhtar Syafa'at Abdul Ghofur. The hidden curriculum implemented includes congregational prayers, madrasah diniyah, istighosah, study sessions of the Ihya’ Ulumiddin book, Quran learning using the Yanbu’a method, monthly Ahad Legi gatherings, and weekly ro’an activities every Friday. This research contributes to uncovering the role of the hidden curriculum as an effective strategy for character development in Islamic boarding schools. It provides a reference for other educational institutions to integrate similar practices into their teaching systems.   Abstrak Kurikulum pendidikan yang diterapkan di pondok pesantren dalam mendidik karakter santri tidak hanya sebatas menggunakan sistem kurikulum yang tertulis saja, ada pula kurikulum tersembunyi yang diterapkan dalam proses kegiatan pengajaran di pondok pesantren. Tujuan penelitian ini adalah untuk menjelaskan mengenai kebijakan hidden curriculum (kurikulum tersembunyi yang ada di Pondok Pesantren Darussalam Blokagung Banyuwangi). Penelitian ini menggunakan metode deskriptif kualitatif, yang menekankan observasi lapangan. Tujuan dari metode ini adalah untuk mendapatkan informasi yang lengkap dan mendalam dengan pengumpulan data berupa observasi, wawancara dan dokumentasi. Penelitian ini menemukan bahwa hidden curriculum yang diterapkan di pondok Pesantren Darussalam Blokagung sudah dilaksanakan sejak zaman pendiri pondok pesantren sendiri, yaitu KH. Mukhtar Syafa’at Abdul Ghofur. Hidden curriculum yang diterapkan meliputi sholat berjamaah, madrasah diniyah, istighosah, pengajian kitab Ihya’ Ulumiddin, pembelajaran Al-Qur'an dengan metode Yanbu’a, pengajian rutin bulanan Ahad Legi, serta kegiatan ro’an santri setiap Jumat. Penelitian ini berkontribusi dalam mengungkap peran hidden curriculum sebagai strategi efektif dalam pembentukan karakter santri di pondok pesantren, serta memberikan referensi bagi institusi pendidikan lain untuk mengintegrasikan praktik serupa dalam sistem pengajarannya. Kata Kunci: hidden curriculum; karakter religius; santri